Efficacy of Rainwater Harvesting Structures on Ground Water Recharge andits Quality in Micro -Watershed. - D.T.Meshram; V.V.App Rao’; B.G.Bagle; D. G. Dhandhar (Journal of Soil and Water Conservation, 2022)
A study was carried out to under stand the effectiveness of water harvesting structures on ground water recharge, reduction of storage capacity due to silt load and quality of water in the wells in a semi arid environment over four years (2002-2005). Two water-harvesting structures and three open wells were constructed for this study. These structures resulted in rise of water table in open wells located downstream to the structure and an appreciable amount of moisture storage in the micro- watershed. The finding of the study indicated that the storage of each water harvesting structure was liable to be reduced due to silt load and seepage losses. However, groundwater recharge from the structures improved the quality of water in the wells by diluting the salt content.